Христианские мотивы в росписях пантикапейских склепов - Зинько, Е.А. (Материалы по археологии, истории и этнографии Таврии, 2003)
Исследования, проводимые мною в последнее десятилетие по изучению позднеантичных пантикапейских склепов, позволили не только картографировать более 220 грунтовых склепов, открьп'ь и полностью изучить несколько новых склепов, среди которых два расписных , но и выделить определенные хронологические этапы в бытовании того или иного типа этих склепов, а также по-новому рассмотреть культовую символику в их росписях. Сейчас известно 11 грунтовых склепов с живописью, выполненной, по определению М.И.Ростовцева, в геометрическом стиле. The problem of religion-sacral sense of “geometric style” in vault painting is examined in this article on the basis of the materials of research of ground vaults in Panticapaeum necropolis on the northern slope of Mithradates Mountain. The author analyzes the main elements in painting in frescos: a grapevine, tree, ship, pichires of animals, geometric figures and others. She shows their relations with religious presentation of early Christians. The tendency to simplification of the topic in wall painting is traced by the example of wall painted ground vaults of Panticapaeum necropolis dating back to the 3rd - 6th centuries. The change in the subject can be called ascetics and eventually its main symbol - cross. This symbol becomes the unique element in painting in Panticapaeum vaults since the end of the 6th century AD.